High-quality Agar and Polyacrylamide Tumor-mimicking Phantom Models for Magnetic Resonance-guided Focused Ultrasound Applications - Sofokleous, Panagiotis; Damianou, Christakis A. (My University, 2024)
Tissue-mimicking phantoms (TMPs) have been used extensively in clinical and nonclinical settings to simulate the thermal effects of focus ultrasound (FUS) technology in real tissue or organs. With recent technological developments in the FUS technology and its monitoring/guided techniques such as ultrasound-guided FUS and magnetic resonance-guided FUS (MRgFUS) the need for TMPs are more important than ever to ensure the safety of the patients before being treated with FUS for a variety of diseases (e.g., cancer or neurological). The purpose of this study was to prepare a tumor-mimicking phantom (TUMP) model that can simulate competently a tumor that is surrounded by healthy tissue.
Keywords: Agar; Focus ultrasound; Magnetic resonance imaging; Phantom; Polyacrylamide; Tumor